Phosphanegold(I) dithiocarbamates, R3PAu[SC(=S)N(iPr)CH2CH2OH] for R=Ph, Cy and Et: role of phosphane-bound R substituents upon in vitro cytotoxicity against MCF-7R breast cancer cells and cell death pathways - Jamaludin, Nazzatush Shimar; Goh, Zheng Jie; Cheah, Yoke Kqueen; Ang, Kok Pian; Sim, Jiun Horng; Khoo, Chai Hoon; Zainal Abidin, Mohd Fairuz; Abdul Halim, Siti Nadiah; Ng, Seik Weng; Seng, Hoi Ling; Tiekink, Edward Richard Tom (Elsevier, 2013)
The synthesis and characterisation of R3PAu[S2CN(iPr)CH2CH2OH], for R = Ph (1), Cy (2) and Et (3)4, is reported. Compounds 1–3 are cytotoxic against the doxorubicin-resistant breast cancer cell line, MCF-7R, with 1 exhibiting greater potency and cytotoxicity than either of doxorubicin and cisplatin. Based on human apoptosis PCR-array analysis, caspase activities, DNA fragmentation, cell apoptotic assays, intracellular reactive oxygen species (ROS) measurements and human topoisomerase I inhibition, induction of apoptosis by 1, and necrosis by 2 and 3, are demonstrated, by both extrinsic and intrinsic pathways. Compound 1 activates the p53 gene, 2 activates only the p73 gene, whereas 3 activates both the p53 and p73 genes. Compounds 1 and 3 activate NF-κB, and each inhibits topoisomerase I.